"Nel suo No sempiterno a tutti i programmi della Joie". Causa ideale e mito di Antigone nel Cardillo addolorato di Anna Maria Ortese (ENTHYMEMA, 2016)
This paper aims at providing some suggestions for the interpretation of Anna Maria Ortese’s novel The Lament of the Linnet, in the light of Lacanian psychoanalysis and of a comparison with the myth of Antigone. The first chapter consists of a brief introduction to the hermeneutical complexity of the work and to the theme of the enigma in a factual and semantic sense. Subsequently, the role of the main character Elmina as object of desire of the three gentlemen from Liegi and as representative of the discourse of the hysteric will be discussed. Lastly, on the basis of probable textual sources, the hypothesis of a hidden presence of Antigone’s myth is put forward. Thus, Elmina would be a figure of utopian desire: her devotion to Hieronymus Käppchen takes the shape of a moral intransigence that evokes in lower, although not less painful, key Antigone’s drama.
Keywords: Antigone; desire; Elmina; Hieronymus Käppchen; myth